2016
DOI: 10.1038/nature20131
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemogenic effects of Ptpn11 activating mutations in the stem cell microenvironment

Abstract: Germline activating mutations of the protein tyrosine phosphatase SHP2 (encoded by PTPN11), a positive regulator of the RAS signalling pathway1, are found in 50% of patients with Noonan syndrome2. These patients have an increased risk of developing leukaemia3, especially juvenile myelomonocytic leukaemia (JMML), a childhood myeloproliferative neoplasm (MPN). Previous studies have demonstrated that mutations in Ptpn11 induce a JMML-like MPN through cell-autonomous mechanisms that are dependent on Shp2 catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
206
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(213 citation statements)
references
References 39 publications
5
206
1
1
Order By: Relevance
“…In another report, Kousteni's group suggests that activating β-catenin mutations in osteoblasts induce AML in mice (29). Very recently, Dong and Yu et al, reported that Ptpn11 mutations in osteoprogenitor and mesenchymal stem cells induced myeloproliferative neoplasm but that the same mutations in endothelial cells or mature osteoblasts did not induce this effect on myeloid cell compartment (30). These reports from different labs suggest that osteogenic niches support leukemia growth and disease progression.…”
Section: Discussionmentioning
confidence: 91%
“…In another report, Kousteni's group suggests that activating β-catenin mutations in osteoblasts induce AML in mice (29). Very recently, Dong and Yu et al, reported that Ptpn11 mutations in osteoprogenitor and mesenchymal stem cells induced myeloproliferative neoplasm but that the same mutations in endothelial cells or mature osteoblasts did not induce this effect on myeloid cell compartment (30). These reports from different labs suggest that osteogenic niches support leukemia growth and disease progression.…”
Section: Discussionmentioning
confidence: 91%
“…2,11 However, the cellular and molecular mechanisms underlying the microenvironment-induced leukemogenesis remain poorly understood. We here demonstrate that Sipa1 deletion results in BM niche alterations leading to the development of MDS/MPN.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that deletion or mutation of functional genes in these niche cells led to MPNs, myelodysplasia, or leukemia [12,[28][29][30][31][32]. These findings and accordingly raised concepts were proved by the clinical transplantation investigations, in which donor-derived hematologic malignancies after hematopoietic stem cell transplantation were diagnosed [33].…”
Section: Oncogenesis In Abnormal Nichesmentioning
confidence: 69%